Réponses

Meilleure réponse !
2013-09-08T20:12:44+02:00
Bonsoir
A) tu dois commencer par la multiplication
A = 7/4 - 24/36 = 63/36- 24/36 = 39/36 = 13/12
B = (3/3-2/3) : (3/3+2/3) = 1/3 : 5/3 = 1/3 x 3/5 = 3/15 = 1/3
C ) tu commences par la multiplication en la simplifiant 7/6x1/14 devient 1/6 x 1/2
   = 5/6 - 1/12+2/3 = 10/12-1/12+8/12 = 17/12
D) (2/3-3/2) : 7/11 =( 4/6-9/6) : 7/11 = -5/6 x 11/7 = -55/42
E = (7/9) : (1/3 -6/3) = 7/9 : -5/3 = 7/9 x -3/5 = - 21/45
F = 6/7 : (5/3-3/3) = 6/7 : 2/3 = 6/7 x 3/2 = 18/14 = 9/7